Diversity and Conservation: Coral Reefs in Lhok Mata-IE Ujung Pancu Aceh Besar - Zulfikar, Teuku Muhammad; Fadhli, Muhammad; Amni, Chairul; Andalia, Nurlena (Universitas Ahmad Dahlan, 2024)
Coral reef diversity is a crucial indicator of marine ecosystems' health and coastal communities' well-being. This study aims to identify the diversity of coral reef species and their conservation efforts in Lhok Mata-Ie Ujung Pancu, Aceh Besar, using the quadratic transect survey method. The results show high diversity, dominated by hard coral species such as Acropora, Montipora, and Porites. However, the region faces serious threats from illegal fishing, pollution, and the impacts of climate change. In response, local communities, governments, and NGOs have implemented various conservation measures, including the establishment of protected areas and coral replanting programs. Such efforts require cross-sector collaboration to balance natural resource utilization with ecosystem protection. This research provides a solid foundation for the sustainable management of coastal areas and coral reefs in the future.